PRODUCTION PLANNING MANAGEMENT INFORMATION SYSTEM ON PATTERN PT.NAVIRI LESTARI - Sairin Sairin; Drs.Sunarto Drs.Sunarto (Jurnal Sistem Informasi, 1997)
At the end of the writing and review of the CTF / PP is the author concludes that inorder to overcome the barriers that exist in this company would have to be a regularplanning / job vacancies are arranged to avoid the production course should besupported by accurate data in the planning process and the data itself can the form ofreports from each relevant divisions and other information.By implementing this system design can launch the planning process to regulate /manage the system of production work with we just call and see this program for thesolution of every problem. And changing the old ways where there are a lot done in asimple data collection and information that is less clear.